Sociodemographic Factors Related To The Use Of Modern Contraception In Sleman Yogyakarta - Hardiyanti, Ajeng; Wahab, Abdul; Ratrikaningtyas, Prima Dhewi (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
The coverage of the use of modern contraception in Sleman exceeded Indonesia’s achievements in 2017-2019. It’s vital to research sociodemographic factors that influence the use of modern contraception in Sleman as an example for other areas. The purpose of this research is to determine the relationship between sociodemographic factors with the recent contraception use. This study is an observational descriptive model using secondary data from HDSS Sleman. Bivariable analysis was carried out using the chi-square test and followed by multivariable analysis using logistic regression. The result showed that the proportion of modern contraceptive use is 54.1%. Sociodemographic factors that significantly related to the use of modern contraception were the husband’s education and the number of children. Husbands with a high level of education (AOR = 0.56; 95% CI: 0.34-0.90) had a 44% lower chance of using modern contraception than husbands with low levels of education. Couples with ≥2 children (AOR = 4.29; 95% CI: 3.41-5.39) were 4.29 times more likely to use modern contraception than couples with 0-1 children. The conclusion is sociodemographic factors significantly related to the use of modern contraceptive methods are the husband’s education and the number of children.